2020
DOI: 10.1093/pm/pnaa110
|View full text |Cite
|
Sign up to set email alerts
|

Online Acceptance and Commitment Therapy for People with Painful Diabetic Neuropathy in the United Kingdom: A Single-Arm Feasibility Trial

Abstract: Objective This study aimed to assess the feasibility of online Acceptance and Commitment Therapy for painful diabetic neuropathy in the United Kingdom and to determine if a larger randomized controlled trial testing treatment efficacy is justified. Methods Participants with painful diabetic neuropathy were recruited online and from hospital services. This was a single-arm study in which all participants received online Accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Although our study presented higher drop‐out rates from pre‐ to post‐intervention (around 50% for both conditions) than those reported in face‐to‐face ACT (Ong et al, 2018) and CFT (e.g., Hudson et al, 2019) interventions, it was in line with those reported in online interventions (e.g., Halamová et al, 2020; Kioskli et al, 2020), suggesting that both conditions are acceptable for CI. Also, the acceptability of both conditions was evaluated through open ended questions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although our study presented higher drop‐out rates from pre‐ to post‐intervention (around 50% for both conditions) than those reported in face‐to‐face ACT (Ong et al, 2018) and CFT (e.g., Hudson et al, 2019) interventions, it was in line with those reported in online interventions (e.g., Halamová et al, 2020; Kioskli et al, 2020), suggesting that both conditions are acceptable for CI. Also, the acceptability of both conditions was evaluated through open ended questions.…”
Section: Discussionsupporting
confidence: 89%
“…Also, ACT's focus on promoting valued based action and acceptance of internal experiences, instead of aiming at cognitive restructuring, makes it an especially fitting approach to CI, where negative illness beliefs and anticipatory distressing thoughts may be indeed realistic (Graham et al, 2016). Online‐delivered ACT has been found effective in promoting mental health and well‐being (see Thompson et al, 2021) and shown promising results in CI (e.g., Kioskli et al, 2020; Lin et al, 2018; Trindade, Guiomar, et al, 2021; Trompetter et al, 2015). However, results suggest no significant difference between online ACT and comparison interventions (see O'Connor et al, 2018), which calls for more thorough investigations on the optimal intervention approaches that best tackle different difficulties and psychological processes (Hacker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible and theoretically consistent that people who are more willing to experience unwanted thoughts and feelings, and more committed to actions guided by their goals, will experience less COVID-19-related fear and avoidance, or less impact on their functioning from these. Under the circumstances of reduced access to treatments, interventions that are designed to foster PF, and can be flexibly delivered online, such as internet-based ACT 27 , 32 , 57 could potentially help address the psychological impact of COVID-19, and its potential implications for functioning and wellbeing in people with chronic pain. ACT is designed to be flexibly applied.…”
Section: Discussionmentioning
confidence: 99%
“…A previous feasibility study of virtual ACT for painful, diabetic PN used 10 online sessions, compared with six sessions in this study 38 . The 30 individuals in that study had a lower completion rate than participants in this pilot (40% vs 83.3%).…”
Section: Discussionmentioning
confidence: 93%